Activity patterns of wintering Great SkuasStercorarius skua - Magnusdottir, Ellen; Leat, Eliza H.K.; Bourgeon, Sophie; Jónsson, Jón E.; Phillips, Richard A.; Strøm, Hallvard; Petersen, Aevar; Hanssen, Sveinn A.; Bustnes, Jan O.; Furness, Robert W. (Bird Study, 2014)
Capsule: Great Skuas Stercorarius skua wintering in different areas spent different amounts of time in flight (foraging or searching for food) and so may be experiencing different feeding conditions. Aims: To compare the daily percentage of time spent in flight (foraging or searching for food) between different wintering areas. Methods: In 2008, loggers equipped with a saltwater sensor were deployed on adult Great Skuas at three colonies in the northeast Atlantic, and the data used to compare foraging activity between the five main wintering areas. Results: The five areas used by 22 Great Skuas in winter were widely separated, from the northwest Atlantic to northwest Africa, and differ substantially in oceanography. The main difference in foraging effort among areas for individuals that were site-faithful was that the percentage of time per day spent in flight off northwest Africa was much lower than elsewhere. Among five birds that travelled between wintering areas, one reduced the percentage of time in flight after switching from Iberia to northwest Africa. Conclusion: The data suggest that feeding conditions were better off northwest Africa than elsewhere, at least during winter 2008/09. This allowed Great Skuas wintering in that region to spend more time resting, so probably reducing their overall energy expenditure.